Analysis of Material Selection in The Book al-Amtsilah al-Tashrifiyah - Afyuddin, Moh Sholeh; Firdaus, Mohammad Anang; Muammaroh, Ani Tazkiyatum (Al Mitsali : Jurnal Penelitian dan Pendidikan Bahasa Arab, 2024)
Teaching materials have an important role in implementing learning. The presence of unique teaching materials in its presentation, such as the book Al-Amtsilah At-Tashrifiyyah, is interesting to study in the preparation of this book because it uses tables instead of matan like in general books and it is widely used as learning material in various institutions so that it can be used as a reference for Arabic language students in making future teaching materials and work in writing. The analysis of the preparation of this book is analyzed using selection theory. The aim of this research is to reveal more in depth the preparation of the material in the book Al-Amtsilah At-Tashrifiyyah through selection theory. In this research, library research was used with a qualitative descriptive approach and analyzed using document analysis and content analysis. The supporting data for this research was extracted from several books including, Jami' Ad-Durus, Al-Qowaid Ash-Shorfiyyah, Al-Maqshud, Al-Kitab, Imam Sibawaih, Syarah Al-Bannani Syarah Sulamul Munawroq, Tashrif Al-Izzy, Tadrij Al- Adani. The results of this research are: Material selection meets aspects of learning objectives, students' abilities, and time required as well as aspects of frequency, range, availability, coverage, learnability.